2021
DOI: 10.3389/fimmu.2021.665818
|View full text |Cite
|
Sign up to set email alerts
|

Role of CCR2+ Myeloid Cells in Inflammation Responses Driven by Expression of a Surfactant Protein-C Mutant in the Alveolar Epithelium

Abstract: Acute inflammatory exacerbations (AIE) represent precipitous deteriorations of a number of chronic lung conditions, including pulmonary fibrosis (PF), chronic obstructive pulmonary disease and asthma. AIEs are marked by diffuse and persistent polycellular alveolitis that profoundly accelerate lung function decline and mortality. In particular, excess monocyte mobilization during AIE and their persistence in the lung have been linked to poor disease outcome. The etiology of AIEs remains quite uncertain, but env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
(109 reference statements)
1
13
0
Order By: Relevance
“…Differential counting of BALF cytospins revealed no alterations in the distribution of monocytes, eosinophils, neutrophils, or lymphocytes ( Figure 4, C and D ). We also assessed immune populations in the lung parenchyma by flow cytometry analysis using a previously published protocol illustrated in Supplemental Figure 5 , A and C ( 34 , 37 , 38 ). When compared with Ptgfr +/+ controls, at D14, the induced I ER -Sftpc I73T /Ptgfr –/– cohort had similar levels of both myeloid and lymphocyte lineages ( Figure 4E and Supplemental Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Differential counting of BALF cytospins revealed no alterations in the distribution of monocytes, eosinophils, neutrophils, or lymphocytes ( Figure 4, C and D ). We also assessed immune populations in the lung parenchyma by flow cytometry analysis using a previously published protocol illustrated in Supplemental Figure 5 , A and C ( 34 , 37 , 38 ). When compared with Ptgfr +/+ controls, at D14, the induced I ER -Sftpc I73T /Ptgfr –/– cohort had similar levels of both myeloid and lymphocyte lineages ( Figure 4E and Supplemental Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Our group and others have identified monocytes and monocytes-derived moieties as a major population undergoing early expansion during chemical induced fibrogenic responses ( Venosa et al, 2016 ; Misharin et al, 2017 ; Aran et al, 2019 ; Reyfman et al, 2019 ; Joshi et al, 2020 ). We have also shown that monocyte/macrophage moieties play important role in the initial stages of acute exacerbations ( Venosa et al, 2019 ; Venosa et al, 2021 ). The clinical paucity of effective targeted monocyte/macrophage anti-fibrotic therapy suggests that there may be additional key players in the tissue remodeling, particularly in those populations where intrinsic epithelial stress (mutations) drives injury, rather than exogenous triggers.…”
Section: Discussionmentioning
confidence: 87%
“…Inflammation is a defense response of the body to stimuli, an important process in the development of tissue damage. When this process continues, the development of a chronic inflammatory state will promote fibrosis formation by increasing proliferation of fibroblast [ 31 , 32 ]. Recent studies have shown that pulmonary fibrosis can be alleviated by altering the inflammatory Milieu [ 33 ].…”
Section: Discussionmentioning
confidence: 99%